2016
DOI: 10.1080/01635581.2016.1159702
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Identified by the Nutritional Risk Index and Poor Prognosis in Advanced Epithelial Ovarian Carcinoma

Abstract: Ovarian cancer is a chronic disease with a risk of malnutrition. Nutritional Risk Index (NRI) has been reported as a simple and accurate tool to assess the nutritional status. We sought to explore the prevalence of malnutrition and its association with survival in ovarian cancer. A retrospective study was conducted in 213 advanced ovarian cancer patients. NRI was calculated before and at the end of treatment using patients' body weight and serum albumin level. Overall survival (OS) and progression-free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 36 publications
2
42
1
Order By: Relevance
“…Several studies have suggested that the progression of hypoalbuminemia is secondary to the serum elevation of CRP, as many cancer patients with hypoalbuminemia already have increased serum CRP levels [32, 33]. Malnutrition, in turn, is related to poor prognosis in patients with cancer [34]. Several previous studies reported that pre-operative low serum albumin levels are an independent predictor of poor survival in ovarian cancer [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the progression of hypoalbuminemia is secondary to the serum elevation of CRP, as many cancer patients with hypoalbuminemia already have increased serum CRP levels [32, 33]. Malnutrition, in turn, is related to poor prognosis in patients with cancer [34]. Several previous studies reported that pre-operative low serum albumin levels are an independent predictor of poor survival in ovarian cancer [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, the relationship between malnutrition and patient outcome has been well established in many cancers 6-9. Several preoperative nutritional-based scores are designed in order to evaluate nutritional risk, postoperative complications and long-term prognosis, such as the Nutritional Risk Index, Mini Nutritional Assessment, and Geriatric assessment 10-12. Despite recommendations, they fail to gain widespread consensus in GC.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation of the indicators reflecting nutritional status with survival in patients with various types of cancer has received much attention in recent years [14][15][16] . Cancer-related malnutrition is frequently caused by activation of systemic inflammation due to cancer progression, resulting in impaired immunity and reduced survival 8,11,17 .…”
Section: Discussionmentioning
confidence: 99%